2015
DOI: 10.1007/s11069-015-2101-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the alongshore variability of optimum rip current escape strategies on a multiple rip-channelled beach

Abstract: Rip currents are a leading cause of drowning on beaches worldwide. How bathers caught in a rip current should attempt to escape has been a subject of recent debate. A numerical model of human bathers escaping from a rip current flow field is applied to a 2-km-long section of the open beach of Biscarrosse, SW France. The study area comprises 4 rip channels that visually appear similar from the beach, but exhibit different morphologies. Simulations are run for 2 representative hazardous summer wave conditions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 68 publications
1
32
0
1
Order By: Relevance
“…This model is intended for use in making broad assumptions about the type of flow that will occur over a given bathymetry, potentially with only visual observations. It is anticipated that a simplified version of this model may be of use to beach safety practitioners who deal with surfzone currents as a bathing hazard (e.g., Castelle, McCarroll, et al, ; McCarroll et al, ). Bathymetric controls are presented on two axes, bathymetric nonuniformity (horizontal) and channel angle (vertical), with idealized bathymetries illustrating typical flow behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This model is intended for use in making broad assumptions about the type of flow that will occur over a given bathymetry, potentially with only visual observations. It is anticipated that a simplified version of this model may be of use to beach safety practitioners who deal with surfzone currents as a bathing hazard (e.g., Castelle, McCarroll, et al, ; McCarroll et al, ). Bathymetric controls are presented on two axes, bathymetric nonuniformity (horizontal) and channel angle (vertical), with idealized bathymetries illustrating typical flow behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This decision was largely based on field tests of rip escape strategies Van Leeuwen et al, 2016), which clearly showed that natural variance in rip flow behavior influences effectiveness of different rip escape strategy strategies. This has also been illustrated by recent numerical modeling studies (McCarroll et al, 2015;Castelle et al, 2016a, b). However, communicating such a complex and mixed message is problematic.…”
Section: Focus Of Questions Example Topicsmentioning
confidence: 95%
“…The key problem is that rip forecasts tend to be generalized for a large region and time, whereas actual rip development and flow behavior is extremely variable over space and time (Castelle et al, 2016a). It is also difficult to predict the potential for rip development without an understanding of the pre-existing nearshore morphology, which itself is difficult to measure directly, remotely, or through numerical modeling.…”
Section: Focus Of Questions Example Topicsmentioning
confidence: 99%
“…In Australia, rips were a factor in 44 % of recorded beach drownings over a seven-year period (Brighton et al, 2013). Recent research has focussed on assessing the effectiveness of various escape strategies for people caught in rips (Miloshis and Stephenson, 2011;McCarroll et al, 2014aMcCarroll et al, , 2015Castelle et al, 2015;Van Leeuwen et al, 2015). The traditional promoted strategy was (and still is in many places) to swim parallel to the shore .…”
Section: Introductionmentioning
confidence: 99%